A wave propagation model of distributed energy absorption system for trains. Issue 5 (3rd September 2019) - Ding, Zhaoyang; Zheng, Zhijun; Yu, Jilin
Abstract: The dynamic response of distributed energy absorption system used as a passive safety device in high-speed trains is investigated with a one-dimensional wave propagation model, in which carriages are modelled with elastic rods and energy absorber layers are described by a rigid-perfectly plastic-locking material model. Three collision scenarios are analyzed by taking the stresses and velocities of the interfaces as control variables and a set of ordinary deferential equations is obtained for each stage of collision, the duration of which is the time for the elastic wave to pass from one end of the rod to the other. A platform phenomenon of response in all stages is observed. A simplified approximate analysis procedure is proposed to analyze the energy absorption capability. It is found that ignoring the elastic wave effect of carriages will lead to a wrong estimate of the energy absorption capability and the contribution of individual energy absorber.